2014
DOI: 10.1371/journal.pone.0093140
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscle microRNAs in Repairing the Neuromuscular Junction

Abstract: microRNAs have been implicated in mediating key aspects of skeletal muscle development and responses to diseases and injury. Recently, we demonstrated that a synaptically enriched microRNA, miR-206, functions to promote maintenance and repair of the neuromuscular junction (NMJ); in mutant mice lacking miR-206, reinnervation is impaired following nerve injury and loss of NMJs is accelerated in a mouse model of amyotrophic lateral sclerosis (ALS). Here, we asked whether other microRNAs play similar roles. One at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 51 publications
8
70
0
Order By: Relevance
“…The axon repellent semaphorin 3A was shown to be expressed by terminal Schwann cells only in fastfatigable neuromuscular junctions of mutant SOD1 mice, thus suggesting a mechanism by which these synapses would exhibit less plasticity in response to ALS and hence would be affected earlier (26). It was also reported that the disease in mutant SOD1 mice progressed faster in the absence of microRNA-206, which has been involved in the regeneration of neuromuscular junctions in response to injury (117,128). The expression of microRNA-206 was selectively up-regulated in fast-twitch muscle, likely as a compensatory mechanism to halt disease progression in this muscle (114).…”
Section: Does Mutant Sod1 Toxicity Affect All Muscles Indistinctly?mentioning
confidence: 95%
“…The axon repellent semaphorin 3A was shown to be expressed by terminal Schwann cells only in fastfatigable neuromuscular junctions of mutant SOD1 mice, thus suggesting a mechanism by which these synapses would exhibit less plasticity in response to ALS and hence would be affected earlier (26). It was also reported that the disease in mutant SOD1 mice progressed faster in the absence of microRNA-206, which has been involved in the regeneration of neuromuscular junctions in response to injury (117,128). The expression of microRNA-206 was selectively up-regulated in fast-twitch muscle, likely as a compensatory mechanism to halt disease progression in this muscle (114).…”
Section: Does Mutant Sod1 Toxicity Affect All Muscles Indistinctly?mentioning
confidence: 95%
“…Several micro-RNAs have been associated with aging [205]. Treatment targets have focused on the role micro-RNAs in the control of myogenic commitment [206] and maintenance of the NMJ [207]. While research on these and other neuromuscular pathways are underway, these potential drugs are some way away from being available to the clinician and the patient and potential adverse effects are yet to be determined.…”
Section: Future Directions In Pharmaceuticalsmentioning
confidence: 99%
“…Four months after nerve scission, the reinnervated muscle was predominantly type II glycolytic fibres, suggesting that miR206 may aid the determination of fibre type via downregulation of MEF2 transcription factor activity [43] . Valdez et al [44] (2014) also examined the role of miR 133b and miR206 on neuromuscular junction repair in injured mice. In miR206 null mice, reinnervation was impaired following nerve injury, and in mice null for -133b and -206 genes the same impaired neuromuscular repair was seen as in single gene miR-206 null mice, whilst in single gene miR-133b null mice development and reinnervation proceeds normally following nerve injury.…”
Section: Establishment Of Neuromuscular Junctionsmentioning
confidence: 99%
“…Notably, the reports of deregulated myomiRs in cancers often reveal significant relation between the myomiR concentration and tumor severity, with greatest disregulation of expression statistically associated with metastasis, or with tumors of high metastatic potential, or with decreasing prospects of patient survival [88,98102] . Yet, double knockout mice lacking both miR-133a1/2 gene alleles [14] do not display an elevated incidence of tumors in any organs or tissues in vivo, similarly animals with knockout of miR-206 expression [46] , or knockdown of miR-133b or double knockdown of -133b/-206 [44] are not reported to be associated with tumors, indicating that the singular lack of myomiR(s) alone is not (usually) sufficient to initiate tumorigenesis. Hence the oncogenic role of the deregulated myomiRs is a significant potentiating one, dysregulating cell signalling pathways in concert with the multiplicity of other molecular and cell environmental changes occurring in the developing tumor.…”
Section: Myomirs and Cancermentioning
confidence: 99%